Penerapan Metode Qudwah Dalam Pembelajaran Akhlak - Yazida Ichsan; M Miftakhurrohman; Muhammad Maulidan Anshori (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
Learning morals in schools is an effort to improve and develop the morals of students in order to have noble morals. Given that morals are not easy to learn by using any learning method, the researcher tries to explain the effectiveness of the application of exemplary methods (qudwah) in moral learning and the impact that accompanies it. This research uses qualitative methods, with data collection techniques sourced from research books and journals that are focused on research topics. The results showed that the application of exemplary methods in moral learning is an effective alternative in the moral development of students and the application of this method is a separate driving force for educators to continue to strive to be better in order to improve the quality of moral education, in order to be able to answer the challenges of the times in religious life. , nation and state. The impact that occurs is that students will always have an increase in good moral character every time, because the habituation that is applied to support the morals of students is not only given on one side.